The trompenaar's organizational cultural model and it's applicability within Malaysia setting in boosting employee engagement - Lim, Choon Hiang (2012)
The purpose of this research is to examine and explore and finding out what is the perceived organizational culture type and employees' engagement level within Malaysia setting, by adopting adopting Trompenaar' s Organizational Culture Model and Gallop Questionnaires Q-12 respectively. This research was done among working Malaysian from various industries. Data were gathered through questionnaires and was being graphically analyzed. Throughout the statistical and graphical analysis - descriptive analysis, it is found that among all four independent variables, Family culture was the most favourable organizational culture, while Guided Missile culture was the most occurring organizational culture and 67% the current Malaysian employees were found to be at the category of''Not Engaged'', where these group of employees putting time but not energy or passion into their work.